Seva as a Form of Faith-Based Social Work in India (Global Journal of Human-Social Science, 2014)
This paper looks at seva as a form of faith-based social work in India. I identified a random sample of 1017 followers of Hindu faith-based organizations having social service projects. These followers are also doers of seva as a form of engagement with the organizations. My purpose was to understand seva through their lens particularly with a focus on their profiles; engagement chronicles (initiation, duration, type of seva, motivation) and perceived implications for self and society. Seva is viewed as having transcendental benefits for self and as having a unique package of moral philosophy and tangible goals of social development.
Keywords: seva; faith-based social work; india; doers of seva; followers